(untitled) (International journal of artificial intelligence, 2026)
The article examines the integration platform as an institutional and digital mechanism that connects economic actors — enterprises, research organizations, higher education institutions, financial institutions and government bodies — into a single innovation network. The purpose of the study is to identify the relationship between the level of integration and the innovative performance of a region, and to substantiate the system of indicators that measure it. Drawing on the 2025 Global Innovation Index data published by the World Intellectual Property Organization (WIPO), the article carries out a comparative analysis of regions with high and low levels of integration. The findings show that the effectiveness of an integration platform is determined not only by the volume of resources (input indicators), but above all by the density and quality of linkages among participants (linkage indicators). The article puts forward institutional recommendations for the transition from a low to a high level of integration.